Evaluation of Tension and Deformation in a Mandibular Toronto Bridge Anchored on Three Fixtures Using Different Framework Materials, Abutment Systems, and Loading Conditions: A FEM Analysis - Grande, Francesco; Cesare, Pozzan Mario; Mochi Zamperoli, Edoardo; Gianoli, Camilla Martina; Mollica, Francesco; Catapano, Santo (European Journal of Dentistry, 2023)
Objective The aim of this study was to investigate by finite element method analysis the behaviour of a three-implant mandible Toronto framework made by three different materials, with two abutment systems and two loading conditions.Materials and Methods Three implants were virtually inserted in a mandible model in positions 3.6, 4.1, and 4.6. Three prosthetic framework bars with the same design and dimension (4.8 × 5.5 mm) were projected. The variables introduced in the computer model were the framework materials (glass fiber reinforced resin, Co-Cr, TiAl6V4), the abutment systems (Multi-Unit-Abutment [MUA]/OT-Bridge), and the loading conditions (500 N vertical load on all the framework area and 400 N on a 7-mm distal cantilever). The computer was programmed with physical properties of the materials as derived from the literature. Maximum tension and deformation values for each variable were registered at framework, screws, and abutment level and then compared.Results Metal frameworks Cr-Co and TiAl6V4 resulted in lower deformation than glass fiber-reinforced resin frameworks while presenting higher tension values. The OT-Bridge exhibited lower maximum tension and deformation values than the MUA system. The first loading condition reached higher tension and deformation values than the second and it resulted in more uniformly distributed load on all the framework area, especially with the OT-Bridge system.Conclusion More rigid materials and OT-Bridge system decrease the deformation on the prosthetic components. Tension stresses are more uniformly distributed with glass fiber-reinforced resin, in the OT-Bridge system and avoiding cantilever loading.
Keywords: All-on-Three; implant; prosthesis; FEM analysis; OT-Bridge; MUA